Efficacy and tolerability of topical fixed combination of nadifloxacin 1% and adapalene 0.1% in the treatment of mild to moderate acne vulgaris in indian patients: A multicenter, open-labelled, prospective study - Bela Jaswantlal Shah; Tharayil Kunneth Sumathy; Rachita Savalaram Dhurat; Raghunandan Govind Torsekar; Vishalakshi Viswanath; Jayesh Ishwardas Mukhi; Ganesh Kadhe; Pashmina Ahirrao (Wolters Kluwer Medknow Publications, 2014)
Background: A combination of topical retinoid and antibacterial therapy is often advocated for acne to enhance therapeutic efficacy. Aims: A preliminary study to evaluate the efficacy and tolerability of a topical fixed combination of nadifloxacin (1%) and adapalene (0.1%) in the treatment of mild to moderate acne in Indian patients. Materials and Methods: This was an open-labeled, phase 3 non-randomized, non-comparative study conducted at five centers (Ahmedabad, Nagpur, Thane, Bangalore, and Mumbai) across India. Of 119 enrolled patients with mild to moderate acne, 117 patients were evaluated at the end of the study for efficacy parameters. A fixed combination of nadifloxacin (1%) and adapalene (0.1%) topical gel was applied at the affected area once at night for a period of 8 weeks. Reduction in the total, inflammatory and non-inflammatory lesion counts from the baseline, investigator global assessment (IGA) and reduction in the severity of acne as per combined acne severity classification were the primary efficacy variables measured at 2 weeks, 4 weeks, and 8 weeks. Results: Overall, 98.3% patients showed a statistically significant progressive reduction in non-inflammatory lesion counts, inflammatory lesion counts, and total lesion counts over the study duration. By the end of 8 weeks, 75% of the patients had their global assessment scores approaching to normal healthy skin score. The adverse events were mild to moderate in severity. Conclusion: This preliminary study shows that a fixed combination of 1% nadifloxacin and 0.1% adapalene topical gel could be an effective and well-tolerated option for the treatment of mild to moderate acne vulgaris. However, further well-controlled, randomized and comparative evaluation of this combination is necessary.